Beristáin, Godoy y la Virgen de Guadalupe. Una confrontación por el espacio público en la Ciudad de México a fines del Siglo XVIII - Torres Puga, Gabriel (El Colegio de México, A.C., 2002)
During the festivities of the virgin of Guadalupe in 1795, a group of criollos garnished a balcony in Mexico City in order to discredit the cathedral's canon, Mariano  Beristain.  The reason for this quarrel was the recent homage paid by Beristain to Spain's ministers' chief, Manuel  Godoy, who had been  accused of insulting religion and devotion to the virgin. The complaints filed with the Inquisition against  Beristain  afford the  possibility of observing some of informal channels of expression at a time when there was a tightening of the control over the press. Moreover, these complaints illustrate the fierce dispute over control of public opinion in Mexico City at the end of the eighteenth century.